AKIBAT HUKUM TERHADAP NOTARIS YANG MENOLAK PEMBUATAN AKTA RIBA DALAM PERSPEKTIF UNDANG-UNDANG NO. 2 TAHUN 2014 JUNCTO UNDANG-UNDANG NO. 30 TAHUN 2004 TENTANG JABATAN NOTARIS DAN HUKUM ISLAM - Airini Batubara, Sonya; Azharuddin, Azharuddin; Yulia, Vendrista (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2023)
Creditworthiness is undeniable for notaries in the banking industry. The problem arises because Muslim notaries are in a dilemma be cause theydo nothave a strong legal framework to refuse to issue Ribawi deeds. For this reason, whatis thelegal relevance ofnotary public activities to the production of deeds that include riba, whatare the legal protections against notaries who refuse to produce deeds that overlap with riba, what are the legal protections against notaries who refuse to produce We need to consider what the impact is. We will upload acts related to usury. Thetype of rsearch in which this work is written is normative-legal in nature and has a descriptive-analytical character. Thedata colection techniqe usedis a literature survey. The analysis usedis qualitative. The legal relationship of the notary profession to deeds, including Riba, is that the notary acts as a record of transactions and as a witness to credit agreements. Legal protections against notaries who refuse to produce documents that overlap with Riba are contained in Article 29(2) of the 1945 Constitution. The right to practice religion that the state must protect. The legal consequences for notaries who refuse to produce deeds related to usury are subject to administrative sanctions under section 85 of the UUJN or the ethical code of notaries under Islamic law, section 3 (4). There is a possibility. According to the law, a Muslim notary will avoid usury charges and his property will be released from haram.